Modeling and Simulation of Digital Scene Image Synthesis Using Image Intensified CCD Under Different Weathers in Scene Matching Simulation System - Xiao, Liang; Wu, Huizhong; Tang, Shuchun; Liu, Yang (Systems Modeling and Simulation: Theory and Applications, 2005)
The synthesis of digital real-time image in scene matching has great significant and application in military. We first propose a practical scene matching simulation system. Then most factors effecting on real time image synthesis including the change of missile’s poses, hypsography, meteorology and the characteristics of image intensified CDD is investigated.The keymathematical models including eradiate aberrance and camera’s aberrance of digital scene image synthesis are discussed. An overall designing framework for simulation system is proposed. Furthermore, a powerful simulated real time image synthesis system named by SMRT-SS oriented to Image Intensified CCD camera is developed. Finally some simulation results are given.